(3GdESaGQ Yf bde GdCXaGQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg gPG LRA aj BOGH bde GdBXaGQ hSejJg CNQL GdTjNGf Yf CHj gQjQI Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B: " (3NeS ef GdaWQI ; GdNJGf hGdGSJMOGO hbU GdTGQH hJbdje GdCXaGQ hfJa GdEHW (B"s
(3BNQgG (B:s
(3hCNQL GHf YSGcQ aj JGjNg Yf GdQjGTj bGd SeYJ GdCUeYj jbhd ONdJ Ydi gGQhf GdQTjO jhe GdLeYI hgh jbde CXaGQg abdJ dg aj Pdc abGd (B: (3CNP GdCXaGQ jhe GdNejS ef GdSfI hGdMeO ddg hMOgs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B1\81s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs